Podnebne spremembe in odnos javnosti do rabe obnovljivih virov energije - Kurdija, Slavko (Teorija in praksa, 2023)
The article presents survey findings concerning public attitudes to renewable energy sources (RES) (SJM 2019/1) within the context of cross-national climate change comparisons from the ESS 2016 Climate Change module. The results indicate a high level of public agreement with the climate change paradigm, yet reticence with respect to concrete environmental measures. Similar findings emerge in the RES study, which shows a strong preference for the wind and solar scenarios, presented in more detail from the public’s perspective, with the advantages and disadvantages. However, when analysing the specific spatial implementation, public opinion slowly has slipped from an environmental to an economic mentality. A comparative analysis of ESS data provides a similar impression, especially when looking at the differences between developed Western European/Nordic countries and Central/Eastern European countries. The authors stress that environmental transformation (including RES implementation) will not be successful without a broader transformation of society which ensures that the benefits and risks are equitably distributed.
Keywords: climate change; ESS; European Social Survey; Evropska družboslovna raziskava; javno mnenje; Javnomnenjske raziskave; Obnovljivi viri energije; podnebne spremembe; prostorski učinki; public opinion; renewable energy; solar farm; sončna elektrarna; spatial effets; vetrna elektrarna; wind farm